The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.ccm.0000169883.41245.23
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin immunoreactivity in cerebrospinal fluid after traumatic brain injury: Clinical and experimental findings

Abstract: CSF ubiquitin levels are increased more than four-fold in patients after TBI and nontraumatic subarachnoid hemorrhage. Peak CSF ubiquitin measurements in patients with TBI probably underestimated the actual peak, on the basis of data from the animal model. The progressive rise in CSF ubiquitin in patients with TBI who died suggests that lack of clearance could reflect lethal progression to irreversible brain damage. Erythrolysis is one potential source of CSF ubiquitin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 19 publications
11
37
0
Order By: Relevance
“…The observation that i.v. AMD3100 did not affect ubiquitin plasma levels further supports the assumption that the majority of extracellular ubiquitin originates from its passive release from cells and tissues undergoing physiological turnover or damage (16)(17)(18)37,56).…”
Section: Discussionsupporting
confidence: 54%
“…The observation that i.v. AMD3100 did not affect ubiquitin plasma levels further supports the assumption that the majority of extracellular ubiquitin originates from its passive release from cells and tissues undergoing physiological turnover or damage (16)(17)(18)37,56).…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies suggested that the majority of extracellular ubiquitin originates from damaged cells and tissues, and we identified erythrocytes as a major source (12,13,48). Although mature erythrocytes contain high amounts of ubiquitin, they have lost substantial amounts of enzymes of the ubiquitin proteasome pathway (4,49).…”
Section: Discussionmentioning
confidence: 99%
“…Hemolysis was estimated spectrophotometrically by measuring plasma absorption at 414 nm with an enzyme-linked immunosorbent assay (ELISA) plate reader (Quant, Bio-Tek Instruments, Winooski, VT) against standard curves of hemolyzed pRBCs. Hemolysis was induced in vitro by a freeze-thaw cycle followed by centrifugation at 20,000 g for 30 min [23].…”
Section: Methodsmentioning
confidence: 99%
“…Its intracellular concentration in RBCs is 10 -20 ng Ub/10 6 cells and the ubiquitin amount per blood volume is 1,000-to 10,000-fold higher in erythrocytes than in any other blood cell type [19 -23]. Recently, hemolysis was identified as one potential source of extracellular Ub in vivo [23]. Ub has well-defined intracellular roles in protein degradation and posttranslational modification [24 -26].…”
Section: Introductionmentioning
confidence: 99%